Case report: Sudden onset optic neuritis shortly after SARS-CoV-2 vaccination in an allogeneic hematopoietic stem cell transplant recipient with chronic graft-vs.-host disease - Chu, Chiang; Jiang, Shin-Kuang; Shao, Yi-Ching; Yeh, Su-Peng (Frontiers in Medicine, 2023)
Hematopoietic stem cell transplantation (HSCT) recipients affected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have a high mortality rate. The American Society of Transplantation and Cellular Therapy (ASTCT) and the European Society for Blood and Marrow Transplantation (EBMT) recommend vaccination for these vulnerable populations. However, emerging data suggested that vaccination might elicit immunological adverse events, including an exacerbation of graft-versus-host disease (GVHD). Herein, we report a case of severe optic neuritis developed shortly after AstraZeneca COVID-19 vaccination in an allogeneic HSCT recipient with underlying chronic GVHD. The patient had a headache 5 days after vaccination, and the disease progressed rapidly to complete blindness 17 days after the vaccination. The diagnosis of optic neuritis was well-confirmed by the presence of an anti-myelin oligodendrocyte glycoprotein antibody and the typical features of MRI image and Ophthalmoscopy. Other differential diagnoses, such as infection or leukemia relapse in the central nervous system (CNS), were carefully excluded. A timely high-dose corticosteroid was administered, and her visual acuity improved rapidly. She returned to her baseline status 1 month later. With more than one year of follow-up, no optic neuritis or leukemia relapse was observed. In summary, allogeneic transplant recipients can develop severe optic neuritis after vaccination. Optic neuritis can be an exacerbation of GVHD or rarely a sporadic adverse event of vaccination. Furthermore, our experience indicates that a prompt diagnosis and early steroid treatment are vital for a good recovery.